Bariatric and metabolic surgery, different surgical techniques and their implications (International Seven Journal of Health Research, 2024)
Introduction: The global increase in obesity has generated an increasing prevalence of this health condition, associated with various clinical conditions. Obesity management may include lifestyle changes, medication use or surgical intervention, such as bariatric surgery. Among the surgical techniques most used in this context, the gastric bypass procedure stands out, recognized for its effectiveness in reducing weight and improving associated comorbidities. Methodology: A bibliographic review was carried out in the PubMed database, covering articles published between 2010 and 2022. The search used key terms such as "gastric bypass", "obesity", "comorbidities" and "effects". Results and Discussion: The analyzes carried out in the studies showed that the gastric bypass procedure proves to be an effective strategy in the management of obesity, promoting a significant reduction in weight and contributing to the improvement of coexisting conditions such as diabetes, high blood pressure, dyslipidemia and sleep apnea. Additionally, gastric bypass has favorable effects on quality of life and reduced mortality rates. Although its effectiveness is notable, the indication for gastric bypass requires careful evaluation, taking into account the severity of obesity and the presence of coexisting conditions. Raising patients' awareness of the risks and benefits of this procedure is imperative, as is the need for post-surgery follow-up by a multidisciplinary team. Conclusion: The gastric bypass procedure emerges as a safe and effective option in the treatment of obesity, having a positive impact on weight reduction, improving coexisting conditions and the quality of life of patients. However, the importance of careful selection for the indication of this technique is highlighted, as well as continuous supervision by a multidisciplinary post-surgery team.